Perfil bacteriológico e determinação da atividade de água de salame tipo italiano em três formas de comercialização no município de Niterói - RJ - Andreoli, Priscila Albuquerque (2009)
Salami belongs to a class of products that are considered ready for consumption. These products usually do not undergo prior heat treatment, thefore their hygienic quality is extremely important to the security of the consumers. Considering the production of italian salami in Brazil and the lack of qualitative information about this kind of product, this study intended to verify the quality of italian salami samples produced by industries inspectioned by the Brazilian federal inspection service. 75 samples of salami (whole, sliced by meat industries and sliced at the supermarket) commercialized in supermarkets in the city of Niterói (RJ) were studied. The following tests were performed: lactic bacteria, positive coagulase Staphylococcus spp., total coliforms, Escherichia coli, Salmonella spp., Enterococcus spp., water activity, serology of a strain isolated of E. coli and antimicrobial susceptibility test of the isolated strains of E. coli and positive coagulase Staphylococcus spp. It was observed that 77.3% of the analyzed samples were considered unsuitable for consumption because of the presence of positive coagulase Staphylococcus spp. above official acceptable limits (BRASIL, 2001).